Understanding assessment in the special education process - Pierangelo, Roger; Giuliani, George (California, 2008)
This book provides general and special education teachers will clear information about the types of assessments that help determine student eligibility for special education services.
Keywords: Children with Disabilities- Rating of --United States; Disability Evaluation- United States; School Grade Placement- United State